SCREENING FOR ANTIOXIDANT ACTIVITY IN TRADITIONALLY USED MEDICINAL HERBS: COMPARISON OF TOTAL PHENOLS, RADICAL SCAVENGING AND DNA DAMAGE PROTECTING ACTIVITY - RACHNA GARG; DEVIHALLI CHIKKAIAH MOHANA; KIRAGANDUR MANJUNATH (International Journal of Pharma and Bio Sciences, 2013)
Herbal infusions of nine traditionally used medicinal plants were screened for total phenolic content (TPC), radical scavenging activity (RSA) and oxidative DNA damage protecting capacity by chemical assays. The TPC was determined in order to know its correlation with RSA. The extracts of T. cordifolia and C. spectabilis presented highest TPC values (34.21 ± 0.93 and 28.36 ± 1.05 mg GAE/g) and showed strong RSA (96.29 ± 0.91 and 84.68 ± 0.90 mg TE/g). A significant relationship (R2 = 0.915, p< 0.01) was found between TPC and RSA indicating that phenolics are contributing to the antioxidant properties of these plants. The qualitative analysis of DNA damage protecting activity revealed the potential of T. cordifolia, V. negundo, O. sanctum and C. phlomides extracts as potent DNA damage protecting agent. Present study validates the uses of these herbs in various herbal ailments to treat many illnesses associated with oxidative stress.